Kajian Laboratorium Laju Resapan Prime Coat Aspal Emulsi Anionik pada Lapis Fondasi Atas - Dwi Putri Tiara Madjegu; Fadly Achmad; Frice Lahmudin Desei (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the infiltration rate of anionic emulsion asphalt used as a prime coat on Class A aggregate base course and to evaluate its compliance with the 2018 Bina Marga General Specifications Revision II. A laboratory experimental method was employed using transparent acrylic cube containers to observe asphalt penetration into the aggregate base over a 48-hour period. Two types of anionic emulsion asphalt, SS-1h and SS-2h, were tested under controlled observation throughout the testing period. The results showed that SS-1h exhibited better infiltration performance than SS-2h, reaching an average penetration depth of 1.47 inches (3.74 cm), with the penetration rate beginning to stabilize after the fourth hour. Nevertheless, the residual asphalt measured after 48 hours was 0.78 l/m² for SS-1h and 0.85 l/m² for SS-2h, both exceeding the specified range of 0.22–0.72 l/m². These findings indicate that although SS-1h provides greater penetration, neither emulsion fully satisfies the residual asphalt requirement. The infiltration process is affected by emulsion breaking, which produces solid bitumen particles that progressively block aggregate pores and restrict fluid movement. This resistance interacts with capillary action, surface tension, and asphalt viscosity, while ambient temperature further influences the infiltration behavior during laboratory testing under study conditions.